Teaching Writing Using Genre-Based Approach in Narrative Text - Pitri Pitri; Tatu Siti Rohbiah; As’ari As’ari (Journal of English Language Teaching and Cultural Studies, 2024)
This research aims to measure the effectiveness of the genre-based approach in teaching narrative text writing in class x at MA Daar Et-Taqwa petir, kabupaten Serang. The number of students in the experimental class was 15 people and in the control class there were 15 people. In this research, the method used is the quasi-experimental method. The sample was selected by using cluster sampling. In collecting data, the researcher used instruments in the form of observation, and written tests for pre-test and post-test. After giving the post-test, the researcher analyzed the data using SPSS version 26.The results of the research show that the difference in the average posttest score of students in the experimental class is 74.46, which is greater than the average posttest score of students in the control class of 63. Based on the t-test value (0.000), it is smaller than the significance level a (0, 05) so it can be concluded that Ho is rejected and Ha is accepted. This shows that there are differences in student learning outcomes in the experimental class when compared with learning outcomes in the control class. Thus, the use of a genre-based approach is effective in teaching writing narrative texts in class x at MA Daar Et-Taqwa Petir, Kabupaten Serang.